Analysis of the problems of Islamic financial literacy for Muslim scholars - Nawir Yuslem; Nurhayati Nurhayati; Ahmad Fauzul Hakim Hasibuan (Faculty of Economics, Universitas Islam Indonesia, 2023)
Purpose – This study aims to investigate the problem of the literacy level on Islamic financial among the Ulama. This study uses data from scholars engaged in the field of da'wah Islamic community organizations, including Nahdatul Ulama, Muhammadiyah, Al-Washliyah, and the Indonesian Ulama Council located in North Sumatra.Methodology – This study employs descriptive qualitative approach with a case study as the research methods. In addition, the Analytic Network Process (ANP) technique with a weighted questionnaire given to informants is also used as the analytical technique. Weighting is done through comparison between criteria and sub-criteria.Findings –The results showed that problem of Islamic financial knowledge (at 29.80 percent) is the highest Islamic financial literacy problem. It then was followed by Islamic financial belief at 25.75 percent, financial attitudes at 16.97 percent, Islamic financial behavior at 17.69 percent, and the lowest was financial skill by 9.77 percent. Furthermore, the rate of agreement value of all respondents at 27 percent implies that the respondent's level of agreement on the priority order of Islamic financial literacy issues in the form of Islamic financial knowledge orientation, Islamic financial beliefs, financial attitudes, Islamic financial behavior, and financial skills is 27 percent.Implications – This research is a reference for regulators in formulating policy strategies to increase Islamic financial literacy in Indonesia.Originality – The novelty of this study is that it identifies the problems of Islamic financial literacy among scholars in North Sumatra by analyzing the opinions of experts from various groups of scholars and stakeholders of Islamic finance.